Dialog Studi Ritual dengan Hermeneutika Tekstual: Suatu Alternatif Berteologi Kontekstual di Indonesia - Sipahutar, Roy Charly HP (Theologia in Loco, 2023)
This article is an attempt to provide an alternative contextual theology in Indonesia. The awareness of Asian and Indonesian theology in recent decades has brought about hermeneutic creativity that seeks to produce a theology that is truly born and belongs to Asia, especially Indonesia. Intertextual hermeneutics, which is popular in the West today, has been developed in Asia to become cross-textual hermeneutics by considering the richness and diversity of Asian cultural and religious texts. However, the certainty that in Asia, especially Indonesia, ritual and oral (speech) traditions have functions that are more rooted and widespread compared to textual (written) traditions demands an alternative hermeneutical model to make non-textual traditions, especially rituals that are preserved amid local communities, has a place in theology. This study uses a descriptive-analytical approach to parse the meaning of ritual, ritual studies (religious material culture), and textual hermeneutics to obtain an alternative to Indonesian contextual hermeneutics. The results of the study indicate that there is a need for dialogue between ritual studies as a form of respect for the authority of Indonesian traditions and textual hermeneutics, which is still dominant in the interpretation of the Scriptures. Dialogue between ritual studies and textual hermeneutics is an alternative to contextual theology in Indonesia.